Biocaps halalan toyyiban / Ahmad Rosli Mohd Nor ... [et al.] - Mohd Nor, Ahmad Rosli; Salam, Nor Lizam Rajulan; Mohamad, Norfadzilah; Abdullah, Siti Ainon; Hashim, Hasnurul Nazimah (2020)
Organic control made from a mixture of natural resources is a most popular alternative in terms of green technology and halal for Muslim use. The innovation has use mixture of Azadirata Indica (AI) and dried chilli as an organic control for Capsicum sp. It can help consumer and farmer to ensure chemical-free and halal pest control tools to apply to their food crops, especially chili. An experiment has been conducted to prove the effevtiveness of the organic pest control to 300 Capsicum sp tree using Random Block Design (RBD). The population has been divided to three (3) treatments group (R2, R3 and R4) and one (1) control group (R1). R2 used organic based pest control (AI), R3 used chemical based pest control while R4 is a combination of Organic and Chemical based. The population placed openly with the control environment and data were taken every two weeks through observations adapted from Srivastava Technique. Until the last week of observation, R2 still remained with a score of 5 (Best) while the other sample got a lower score. In summary, the use of AI mixture as an organic control in the cultivation of Capsicum sp is very effective for the growth of healthy and disease-free Capsicum sp.